Pelatihan Identifikasi dan Pemilihan Makanan serta Minuman Halal untuk Meningkatkan Kesadaran Siswa tentang Konsumsi Halal - Syakira, Elsa; Fajariani, Desta Puji; Az-Zahra, Nova Shella Rida; Adinugraha, Hendri Hermawan; Gunawan, Ade; Sholihah, Ria Anisatus (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
The Human life cannot be separated from its environment, even in terms of consuming food and drink. Muslims must follow halal rules in Islam when consuming food and drinks. This service activity was carried out to improve the understanding and attitudes of grade IV students of MI Izzul Islam Jetak Kidul, Wonopringgo Pekalongan, regarding halal food and drinks. Starting with the preparation, implementation and evaluation stages, partners are empowered with an educational and discussion approach. In the implementation stage, the methods used were lectures, questions and answers and gift giving. The evaluation results showed that after education, there was a significant increase in understanding (20% for male students and 40% for female students). Based on the objectives mentioned, it can be concluded that this service activity has succeeded in increasing the understanding and attitude of grade IV students at MI Izzul Islam Jetak Kidul towards halal food and drinks.